Desperate identities - Langman, Peter (Criminology & public policy, 2020)
Research In this article, I provide a qualitative analysis of ten perpetrators of mass violence, including five school shooters and five attackers in nonschool settings (a random public shooting, a familicide, and three attacks by White supremacist homegrown violent extremists). The killers are discussed in terms of body-related issues, three psychological categories (psychopathic, psychotic, and traumatized), and social failures. I describe how the attackers sought to overcome their perceived inadequacy, framed as damaged masculinity, through acts of violence. I also demonstrate the many factors that contribute to acts of mass violence. Policy Implications Violence prevention can be supported by policy initiatives in multiple domains, including mandating the use of threat assessment in educational settings, government support for expanding the use of threat assessment across the nation, training professionals engaged in threat assessment in the broad factors that contribute to mass violence, educating the public about mental health issues, destigmatizing the use of mental health services, increasing access to mental health treatment, and improving child protective services.